Study on the evolution characteristics of spatial network structure of regional agricultural carbon emission reduction capacity based on SNA - Li, Yue; Wang, Zhong; Cao, Yuqing; Wang, Yundi; Yu, Lefei; Zhang, Yue; Tang, Hao (Frontiers in Sustainable Food Systems, 2025)
IntroductionWithin the context of “dual carbon,” exploring the characteristics of the spatial network structure of regional agricultural carbon emission reduction capacity (ACERC) is beneficial to improve regional sustainable development capacity.MethodsTaking Sichuan Province as the case area, this research evaluates the regional ACERC and analyzes its spatial and temporal evolution characteristics by collecting agricultural-related data from 2010 to 2021 from all cities in Sichuan Province using the EWM-TOPSIS model. Combined with the modified gravity model, this paper investigates the spatial correlation strength of regional ACERC. Then, using social network analysis (SNA), the spatial network structure and its formation mechanism are explored.Results and discussionThe research findings indicate that: (1) The ACERC of most cities in Sichuan shows a declining trend, with distinct regional clustering characteristics. The spatial effects of ACERC have transcended geographical proximity to form a complex spatial network. (2) The spatial network structure of ACERC in Sichuan exhibits strong connectivity and a loosening hierarchical structure, but network stability is declining. (3) Cities such as Neijiang, Zigong, and Mianyang occupy central positions within the network, playing the role of central actors. (4) Differences in information-level, rural residents’ income, government importance, and agricultural labor force contribute to the formation of the spatial association network of ACERC. The findings of this study can assist decision-makers in identifying the interconnections and formation mechanisms of ACERC among cities, providing a reference basis for agricultural regional collaborative carbon emission reduction measures.